Delirando o presente: o ethos discursivo em canções afrodiaspóricas perspectiva afrofuturista - Oliveira, Helena Lucas Rodrigues de (2021)
This dissertation aims to investigate the construction of the discursive ethos in the songs from the album Corpura, by Aláfia, a music band from São Paulo. In 2015, the band won the “Betting” category of the Natura Musical Award, which resulted in the release of this album. As this work aims to highlight the African heritage in the formation of the Brazilian national identity, expressing the need to observe how the contemporary social experiences of the Brazilian black population dialogue with the past and project themselves into the future, the hypothesis of existence of a Triad of (re)awareness, which consistsof the three songs that make up the reference corpus: Salve Geral, Preto Cismado and Proteja seu Quilombo. In addition to the lyrics, the artistic design of the booklet and the invitations for the singles' releases are also analyzed in order to verify thegeneric valence and the agency. For this, we used the theoretical-methodological framework of French Discourse Analysis, in its enunciative-discursive aspect, especially the works of Dominique Maingueneau, in which the concepts of Primacy of interdiscourse, simulacrum, scene of enunciation and discursive ethos are found. The results show that the hypothesis of the Triad of (re)awareness was confirmed and from these songs a discursive ethos emerges that can be compared to the principles of Afrofuturism, that is, that summons, demarcates and reinforces a place of possibilities in the present to realize a future based on the reconstruction of historical episodes from the past